The Image of Women Characters in The Novel Andini by Santy Diliana (A Feminism Approach) - Lestari, Nunik Deti (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This study aims to describe the image of the female character in the novel Andini by Santy Diliana which is studied from the physical and psychological aspects. This research is a type of qualitative research. The data obtained in this study are in the form of information which is used as the object of study, namely every word, sentence, and sentence of expression that supports physical and psychological aspects. Data were analyzed with qualitative analysis techniques. The results of the study show that the image of female characters is divided into two, namely the self-image of women seen from the physical and psychological aspects depicted in Andini's novel are adult women, women who have entered the level of maturity and experience changes in themselves, namely biologically adult women are characterized by signs -physical signs, such as experiencing menstruation, being able to get pregnant, give birth, and breastfeed their children. The image of female characters from the psychological aspect depicted in this novel is that women are imaged from their psychological state when facing problems from within their families and from outside the environment and trying to control their inner emotions in dealing with their respective problems.